Matematyka
akinom111
2017-06-26 16:40:39
[latex] int { frac{2+cosx}{sin2x} } , dx [/latex]
Odpowiedź
moniczka0804
2017-06-26 20:47:18

[latex] frac{1}{sin(2x)}=csc(2x) \ intfrac{2+cos(x)}{sin(2x)} dx = int (cos(x)+2) csc(2x) dx = \ [/latex][latex]int(2csc(2x)+cos(x)csc(2x))dx=int frac{csc(x)}{2} dx + 2 int csc(2x)dx= \ [/latex] [latex] =frac{1}{2} int - frac{-ctg(x)csc(x)-csc ^{2}(x) }{ctg(x)+csc(x)} dx+2 int csc(2x)dx= \ [/latex] [latex]u=ctg(x)+csc(x)\ du=(-csc ^{2}(x)-ctg(x)csc(x)) \ = frac{1}{2} int - frac{1}{u} du+2 int csc(2x)dx= \ [/latex] [latex]=- frac{1}{2} int frac{1}{u} du +2 int csc(2x)dx =- frac{log(u)}{2}+2 intcsc(2x)dx= \ s =2x \ ds=2dx \ =- frac{log(u)}{2} +int csc(s)ds= \ [/latex] [latex]= -log(ctg(s)+csc(s)) - frac{log(u)}{2} = \ s=2x \= - frac{log(u)}{2}-log(ctg(x))= \ u=ctg(x) +csc(x) \ =-log(ctg(x))- frac{1}{2}log(ctg(x)+csc(x))= \ [/latex] [latex]= frac{1}{2} (log(sin( frac{x}{2} ))+2log(sin(x))-log(cos( frac{x}{2}))-2log(cos(x)))+c[/latex]

Dodaj swoją odpowiedź